Pelanggaran Maksim Relevansi Terdakwa Putri Chandrawati dalam Persidangan Kasus Ferdy Sambo pada Laman Kompas TV - Aulia, Dhannisa; Risagarniwa, Yuyu Yohana; Ardiyati, Riza Lupi (Universitas Muhammadiyah Surabaya, 2024)
The Ferdy Sambo case was one of the significant cases that drew the attention of the Indonesian public. Throughout the trial, the case was broadcast live on several Indonesian television channels, especially Kompas TV. The purpose of this study is to show how the defendants Putri Chandrawati violated the concept of maxims relevance during the trial in the Ferdy Sambo case. Floating maxims of relevance become the focus on this study. The author concentrates on the defendant's transgressions, but the conversation was between the judges and the defendants. The researcher used six data sets as examples to describe and examine further. The author concludes that floating maxims of relevance committed by the defendant might result in awkwardness and inadequate communication, making it impossible for the court to get clear and relevant information. This study used the note-taking approach in conjunction with a descriptive qualitative method. Since the data source is Kompas TV's official YouTube channel, the author does not require extra authorization to collect voice data.